2023
DOI: 10.5796/electrochemistry.23-00088
|View full text |Cite
|
Sign up to set email alerts
|

NASICON-type Li<sub>1.5</sub>Al<sub>0.5</sub>Ge<sub>1.5</sub>(PO<sub>4</sub>)<sub>3</sub> Containing Amorphous Phase for Solid Li-Ion Conductor

Yoichiro KAWANO,
Akihiko KATO,
Hiroyuki USUI
et al.

Abstract: Amorphous Li 1.5 Al 0.5 Ge 1.5 (PO 4 ) 3 (LAGP), which is an oxide-based solid electrolyte with a NASICON-type structure, was sintered at various temperatures to investigate its ionic conductivity and potential windows. The LAGP sheet sintered at 600 °C exhibited a slightly diminished ionic conductivity in comparison to that sintered at 800 °C; however, it effectively suppressed the current density value for oxidative decomposition around 5 V vs. Li + /Li. The crystal structure of the sintered LAGP sheets was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 13 publications
(20 reference statements)
0
2
0
Order By: Relevance
“…2,19 Similarly, we already confirmed that GeO 2 is formed at higher sintering temperatures of amorphous LAGP. 20 It was attributed to the presence of amorphous GeO 2 in the amorphous LAGP. Amorphous LAGP is obtained by melting the raw materials of LAGP at 1300 °C and quenching the melt assuming that a small amount of Li volatilizes during the sintering process.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2,19 Similarly, we already confirmed that GeO 2 is formed at higher sintering temperatures of amorphous LAGP. 20 It was attributed to the presence of amorphous GeO 2 in the amorphous LAGP. Amorphous LAGP is obtained by melting the raw materials of LAGP at 1300 °C and quenching the melt assuming that a small amount of Li volatilizes during the sintering process.…”
Section: Resultsmentioning
confidence: 99%
“…We have already reported the results of our investigation into the redox behavior of LAGP sintered at 600 °C. 20 The calculations of the electronic density of states for the constituent elements of LAGP using first-principles calculations indicates significant influences on Ge and O at the lowest position of the conduction band on the reduction side. A reduction of GeO is expected, and some reduction of P is also implied.…”
mentioning
confidence: 99%